The housing subject in bogota: from the territory to the country´s central region (2006)
The present article analyze the scene from where the subject of housing in Bogotá, framed by recent proposal (2004) to conform the central region, CR, of the country, and the information gathered by interdisciplinary team works, in a pair of researches made from the Center of Academic Extension , CAE, of the Art’s faculty. It is tried, then, to contribute new elements about population growth and the migrations to this territory, with the intention to evidence the strong relation between housing-growth and migrations.